Gruzja - "druga ojczyzna" Borysa Pasternaka = Georgia - "The Second Homeland" of Boris Pasternak - Zbyrowski, Zygmunt (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Pasternak stayed in Georgia upon several occasions, the longest visit being three months in 1931. There, he made the acquaintance of and befriended a number of outstanding Georgian poets. A direct contact with the nature, culture and inhabitants of Georgia as well as Georgian sympathy and kindness exerted an impact upon his emotions and oeuvre.
Keywords: Pasternak, Borys Leonidowicz (rosyjski poeta i prozaik; 1890-1960); Gruzja a Rosja - kultura; literatura rosyjska; literatura - tematyka; 20 w.